The White Center. A First Step of the Civic Remembrance System in Bon Pastor (Barcelona) - Remesar, Antoni; Crespo-Martin, Bibiana (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
Following the development in 2011 of the Mural of Remembrance in Baró de Viver (Barcelona) the adjacent district of Bon Pastor, showed interest in a symbolic and artistic element of similar characteristics. However, from the beginning, Bon Pastor neighbours expressed the idea that writing their remembrance should not be performed on a linear support, but should be distributed by the territory. The research team of the Polis Research Centre started a participatory process (not yet completed) within the framework of cooperation agreements between the Centre, the Neighbourhood association and the local authorities of the Sant Andreu district. At the same time, the subject of this “memory space system” became a topic to be developed by one of the, interdisciplinary and international, teams of students of the Master in Urban Design, Universitat de Barcelona. This article presents the progress made.